Kualitas Batuan Beku sebagai Bahan Konstruksi pada Daerah Warmare Kabupaten Manokwari - Angelina M. Randa; Rana Wiratama; Eric A. Patandianan; Irman Irman (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2022)
Madrad area, Warmare District, based on field appearances, found a lot of igneous rock fragments in the river found at the research location which were considered to have potential sources of C minerals, especially in andesite-basaltic rocks which are the lithological units that make up the Arfak volcanic formation found at the research location. The purpose of the study was to determine the quality of igneous rocks included in the Arfak Volcano Formation in Madrad and its surroundings based on the type of utilization. The method used is literature study, collecting field data in the form of geological conditions of the research area and taking rock samples, then laboratory analysis in the form of compressive strength tests, petrographic analysis. The Compressive Strength Test used is Uniaxial Compressive Strength. The purpose of the compressive test is to measure the uniaxial compressive strength of a rock sample in a regular geometry, either in the form of a cylinder, beam or prism in one direction (uniaxial). So that the test results can be classified the strength and characteristics of the rock. From the results of laboratory testing, samples of Basalt and Andesite igneous rocks obtained in the research area can be used as concrete piles for Basalt rock types and as road concrete for Andesite rocks (Standard Directorate General of Highways, 1976).